Lampedusa - Price, Steven 1976- (Picador, 2019)
"In the Sicily of the ’50s, still haunted by memories of Fascism and the war, Giuseppe Tomasi, the last Prince of Lampedusa, struggles to complete the novel that will be his lasting legacy, The Leopard. In 1943, an Allied bomb destroyed the Lampedusa palace in Palermo; in 1955, Giuseppe Tomasi is diagnosed with advanced emphysema. Shortly after, profoundly aware of his mortality, he begins work on a novel, imagining the life of his great-grandfather Don Giulio, astronomer prince and head of the family at the time of the Risorgimento. Giuseppe Tomasi is a veteran of the previous war, while his wife Alexandra – ‘Licy’ – a Baltic German aristocrat, now lives in exile, after her native Latvia was absorbed into the Soviet Union. The childless couple are survivors of a vanishing world of European aristocracy, living in the present yet profoundly aware of the past."--Provided by publisher
"First published in 2019 by McClelland & Stewart, a division of Penguin Random House Canada Limited"--Title page verso
Keywords: Tomasi di Lampedusa, Giuseppe / 1896-1957 / Fiction; Tomasi di Lampedusa, Giuseppe / 1896-1957 / Family / Fiction; Nobility / Italy / Fiction; Authors, Italian / Fiction; Terminally ill / Fiction; Husband and wife / Fiction; Nineteen fifties / Fiction; Sicily (Italy) / History / 20th century / Fiction; Italy / History / 1914-1945 / Fiction; Italy / History / 1945-1976 / Fiction; Tomasi di Lampedusa, Giuseppe / 1896-1957; Authors, Italian; Families; Husband and wife; Nineteen fifties; Nobility; Terminally ill; Italy; Italy / Sicily; 1900-1999; Biographical fiction; Fiction; Historical fiction; History